The sublime and its teleology : Kant, German idealism, phenomenology - Loose, Donald, 1949- (Critical Studies in German Idealism, 2012)
What are we talking about when we qualify something as sublime? Is it just a qualification of the beautiful in its most touching degree? Is it a qualification of something ouside there anyway? Is it a feeling or a reflecting judgment on aesthetic appreciation? And can we reduce the sublime to the aesthetic? The authors of this book all take the analysis of Kant in \'Critique of the Power of Judgment\' as their primary reference. The argument of this book however is to show in what way the Kantian legacy on this topic is still a main stream of inspiration for contemporary thinking, whether in line with Kant or overcoming his primary impetus for modern philosophy of freedom in a critical reception.